2021
DOI: 10.3389/fonc.2021.677111
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein NELFE Promotes Gastric Cancer Growth and Metastasis Through E2F2

Abstract: Worldwide, the incidence rate of gastric cancer ranks fifth, and the mortality rate of gastric cancer ranks third among all malignant tumors. However, the pathogenesis of gastric cancer remains poorly understood. In this study, we demonstrated that the expression level of NELFE is higher in human gastric cancer tissues than in adjacent nontumor tissues. A high level of NELFE is associated with worse postoperative overall survival (OS) and relapse-free survival (RFS) rates in patients with gastric cancer. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…E2F2 is essential for B-Myb-induced malignant phenotype, and show positively correlation with B-Myb, interacting in colorectal cancer cells to activate ERK and AKT signaling pathways to promote carcinogenesis [ 36 ]. In gastric cancer, reducing the expression level of E2F2 inhibited the proliferation and migration of gastric cancer cells [ 37 ]. All of these genes have been reported to be involved in cancer development, migration, and invasion, and in-depth studies of these genes have the potential to discover novel bladder cancer target molecules.…”
Section: Discussionmentioning
confidence: 99%
“…E2F2 is essential for B-Myb-induced malignant phenotype, and show positively correlation with B-Myb, interacting in colorectal cancer cells to activate ERK and AKT signaling pathways to promote carcinogenesis [ 36 ]. In gastric cancer, reducing the expression level of E2F2 inhibited the proliferation and migration of gastric cancer cells [ 37 ]. All of these genes have been reported to be involved in cancer development, migration, and invasion, and in-depth studies of these genes have the potential to discover novel bladder cancer target molecules.…”
Section: Discussionmentioning
confidence: 99%
“…E2F2 has been extensively researched in the past few decades in association with gastric cancer. It has been shown that high E2F2 levels are associated with a poor prognosis [19]. A further function of E2F2 is that it regulates PI3K/Akt/mTOR, which are necessary for cell migration, invasion, and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…E2F2 also had potential modulatory effects on tumor immunity. CIBERSORTx analysis of the proportion of tumor-infiltrating immune cells (TICs) revealed that immune cells are correlated with E2F2 expression, suggesting that E2F2 might be responsible for the preservation of the immunodominant status for gastric cancer ( 68 ).…”
Section: Functions Of E2f2 In Specific Cancer Typesmentioning
confidence: 99%